Lindernia barthlottii (Linderniaceae), a new species from inselbergs in Madagascar - Fischer, Eberhard; Andriantiana, Jacky Lucien; Sieder, Anton (Phytotaxa, 2023)
The new species Lindernia barthlottii from an inselberg in Northern Madagascar is described and illustrated. It differs from all Madagascan Lindernia species in the small rosulate habit with condensed stems, the broad obtuse sepals, and the large and except for the palate entirely blue corolla. A short discussion on the other four species of Linderniaceae (Linderniella cerastioides, L. horombensis, L. pygmaea, Crepidorhopalon microcarpaeoides) endemic to inselbergs in Madagascar is provided.